Mandatory Zakat Law Mashlahat Perspective (Philosophical Analysis in Optimizing the Potential of Zakat in Indonesia) - Muhammad Saleh (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This study discusses the urgency of reforming the zakat law in Indonesia from a voluntary system to a mandatory system from a maslahat perspective. Using a philosophical approach, this study analyzes the potential for optimizing zakat through three main theories: legal certainty, legal utility, and the theory of maslahat. In the context of legal certainty, the mandatory system will provide a solid foundation for implementing zakat, ensuring that every Muslim fulfills this obligation in an orderly manner. Regarding legal benefits, binding regulations are believed to increase the collection of zakat, which is then used for poverty alleviation and economic empowerment. Meanwhile, within the framework of the theory of maslahat, this change in regulations is considered to be able to realize social justice and common welfare as the primary goal of Islamic law. This study concludes that implementing the mandatory zakat system requires strong legal support, infrastructure readiness, and public education to increase collective awareness. This reform is expected to be a strategic solution to optimize the potential of zakat as an Islamic social financial instrument in Indonesia.